2022
DOI: 10.3390/cells11060974
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic Variants in ENDOG Associated with Mitochondrial Myopathy and Multiple mtDNA Deletions

Abstract: Endonuclease G (ENDOG) is a nuclear-encoded mitochondrial-localized nuclease. Although its precise biological function remains unclear, its proximity to mitochondrial DNA (mtDNA) makes it an excellent candidate to participate in mtDNA replication, metabolism and maintenance. Indeed, several roles for ENDOG have been hypothesized, including maturation of RNA primers during mtDNA replication, splicing of polycistronic transcripts and mtDNA repair. To date, ENDOG has been deemed as a determinant of cardiac hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…4 ). Additionally, a case report of a patient with biallelic ENDOG mutations described a patient who had a myopathy with multiple mtDNA deletions in muscle, similar to our proband [ 36 , 48 ]. On the other hand, Endog’s IMS localisation and the absence of a mtDNA deletion phenotype in livers of Endog KO mice are plausible arguments against its involvement in the mechanism of mtDNA deletion formation in Chchd10 mutant mice (although that study analysed deletions with a southern blot, which is less sensitive than long-range PCR) [ 49 ].…”
Section: Discussionmentioning
confidence: 54%
“…4 ). Additionally, a case report of a patient with biallelic ENDOG mutations described a patient who had a myopathy with multiple mtDNA deletions in muscle, similar to our proband [ 36 , 48 ]. On the other hand, Endog’s IMS localisation and the absence of a mtDNA deletion phenotype in livers of Endog KO mice are plausible arguments against its involvement in the mechanism of mtDNA deletion formation in Chchd10 mutant mice (although that study analysed deletions with a southern blot, which is less sensitive than long-range PCR) [ 49 ].…”
Section: Discussionmentioning
confidence: 54%
“…Further, the role of critical role of ENDOG in physiological mitochondrial bioenergetics in vivo has been demonstrated, as deletion of Endog in mice resulted in hearts with depleted and dysfunctional mitochondria, resulting in impaired mitochondrial respiration [ 72 ]. In this regard it has long been suggested that ENDOG may play a critical role in mitochondrial DNA replication and repair (which would clearly impact upon OxPhos), and the recent observation of mutations in EndoG that associate with mitochondrial myopathy and multiple mtDNA deletions would strongly support this [ 73 ].…”
Section: Discussionmentioning
confidence: 99%